The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s40964-020-00146-2
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of stiffener geometry on flexural properties of 3D printed polylactic acid (PLA) beams

Abstract: We used finite element analyses (FEA) on Abaqus to study flexural properties of additive manufactured beams using polylactic acid (PLA) polymer. Experimental stress–strain data from flexural testing are used to define elastic–plastic properties of the material in the computation software. The flexural experiments are used to validate the FEA approach suggested. The method provides good results of deflection and stress with errors well below 10% in most of the cases. Therefore, by using the proposed approach, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…It is clear from this figure that the mean deflection at break was raging between 8.39 mm obtained at Test number 3 and 13.85 mm achieved during the experiments of Test 4. These results were in agreement with the deflection at break reported in previous studies [24,25]. From the main effect plot for deflection at break shown in Figure 12, it is observed that the bending deflection at break will be maximal for velocity of 70 mm/s, extrusion temperature of 190 °C, and raster orientation of 0 degree.…”
Section: The Maximum Deflectionsupporting
confidence: 92%
“…It is clear from this figure that the mean deflection at break was raging between 8.39 mm obtained at Test number 3 and 13.85 mm achieved during the experiments of Test 4. These results were in agreement with the deflection at break reported in previous studies [24,25]. From the main effect plot for deflection at break shown in Figure 12, it is observed that the bending deflection at break will be maximal for velocity of 70 mm/s, extrusion temperature of 190 °C, and raster orientation of 0 degree.…”
Section: The Maximum Deflectionsupporting
confidence: 92%
“…In the study of Abouelmajd et al [ 73 ], they stated that the average error between the flexural strength values found between the experimental and FEA analysis was at the level of 5%. Gebrehiwot et al [ 74 ], on the other hand, stated that the average error between the numerical and experimental results of the deflection and strength values of PLA flexural samples produced by the FDM technique was below 10%. Accordingly, it is seen that the results of the FEA are in good agreement with the experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…Using lightweight sandwich structures with proper core topology have many advantages such as high stiffness-to-weight ratio and high energy absorption capability [6]. Conventional methods used to manufacture the sandwich structures have many limitations for the structures with different geometries [7], while, the additive manufacturing (AM) is the state-of-the-art technology that changed the conventional approach to manufacturing systems [8]. 3D printing is an additive manufacturing technique widely used in the automotive and civil construction systems to obtain lightweight sandwich structures made with complex core shapes to achieve excellent multifunctional properties, such as flexural stiffness, and high energyabsorption capabilities [9].…”
Section: Introductionmentioning
confidence: 99%